Research advances of cell signaling involved in appressorium development of Magnaporthe grisea - LI De-bao; JIN Qing-chao; DONG Hai-tao (浙江大学学报. 农业与生命科学版, 2006)
Appressorium initiation, formation and maturation are prerequisites for penetrating into the host tissues by Magnaporthe grisea. As responses to a variety of extracellular signals, cAMP signaling, mitogen-activated protein kinase signaling, and Ca2+ signaling pathways can regulate appressorium development of the pathogen fungus. This review takes a brief walk down molecular mechanism of appressorium initiation, development of M. grisea based on three types of pathways above, focusing on which genes are involved in the pathways and what's the relationship among these different pathways.